Syncope vs. Seizure: Ictal Bradycardia and Ictal Asystole - Sumika Ouchida; Kaitlyn Parratt; Armin Nikpour; Greg Fairbrother (Case Reports in Neurological Medicine)
Background. Ictal arrhythmia is a rare condition that causes arrhythmic manifestations induced by epileptic seizures, including asystole or bradycardia. Ictal asystole (IA) is a very rare condition found in patients undergoing video-encephalography (EEG) monitoring. It is often related to temporal lobe epilepsy and can cause syncope, which can lead to injury or even death. Case Presentation. Two patients with epilepsy showed symptoms of syncope. Both patients underwent 4-day ambulatory EEG tests and were diagnosed with IA. Following the tests, the patients were implanted with a permanent pacemaker, and one of them underwent a temporal lobectomy. As a result of these procedures, the patients experienced a reduction in episodes of symptomatic syncope. Conclusion. Patients with ictal asystole and symptomatic ictal bradycardia are at increased risk of falls due to seizures. Although there are no specific guidelines for managing this condition, antiseizure medications, epilepsy surgery, and cardiac pacemaker implantation have been effective treatments.